2021
DOI: 10.1111/apt.16531
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: neoplasia detection rate and post‐endoscopy Barrett's neoplasia in Barrett's oesophagus

Abstract: Summary Background Neoplasia detection rate, the proportion of Barrett's oesophagus patients with high‐grade dysplasia or oesophageal adenocarcinoma detected at index surveillance endoscopy has been proposed as a quality metric. However, the correlation between neoplasia detection rate and a clinically relevant outcome like post‐endoscopy Barrett's neoplasia remains unknown. Post‐endoscopy Barrett's neoplasia refers to the rate of high‐grade dysplasia or oesophageal adenocarcinoma on repeat endoscopy within on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In another cohort of 13 159 patients diagnosed with high-grade dysplasia or esophageal adenocarcinoma, 12.7% (34/267) were identified within 3 to 12 months after Barrett esophagus diagnosis and were considered to have possibly been missed during index endoscopy, with 25% of these occurring among patients with Barrett esophagus with low-grade dysplasia and 9% occurring among those with nondysplastic Barrett esophagus . To improve detection of dysplasia, a neoplasia detection rate (rate of high-grade dysplasia or esophageal adenocarcinoma detection during initial surveillance endoscopy) is recommended as a validated quality measure for endoscopic evaluation of patients with Barrett esophagus, with data indicating that every 1% increase of neoplasia detection rate leads to a clinically relevant 3.5% decrease in the rate of later diagnosis of Barrett esophagus neoplasia presumed to have been missed at the index endoscopy …”
Section: Progression Of Barrett Esophagus To Esophageal Adenocarcinomamentioning
confidence: 99%
“…In another cohort of 13 159 patients diagnosed with high-grade dysplasia or esophageal adenocarcinoma, 12.7% (34/267) were identified within 3 to 12 months after Barrett esophagus diagnosis and were considered to have possibly been missed during index endoscopy, with 25% of these occurring among patients with Barrett esophagus with low-grade dysplasia and 9% occurring among those with nondysplastic Barrett esophagus . To improve detection of dysplasia, a neoplasia detection rate (rate of high-grade dysplasia or esophageal adenocarcinoma detection during initial surveillance endoscopy) is recommended as a validated quality measure for endoscopic evaluation of patients with Barrett esophagus, with data indicating that every 1% increase of neoplasia detection rate leads to a clinically relevant 3.5% decrease in the rate of later diagnosis of Barrett esophagus neoplasia presumed to have been missed at the index endoscopy …”
Section: Progression Of Barrett Esophagus To Esophageal Adenocarcinomamentioning
confidence: 99%
“…Recent reported NDRs have ranged from 4.9% to 7.0%. 6,[12][13][14] This measurement was developed akin to the concept of the adenoma detection rate (ADR) in colonoscopy, which reflects the quality and effectiveness of the examination. ADR is a percentage of colonoscopic examinations where polyps (adenomas) were detected in comprehensive examinations.…”
Section: Neoplasia Detection Rate (Ndr)mentioning
confidence: 99%
“…Despite these limitations, NDR and the development of Barrett's neoplastic lesions may have an inverse relationship. In a systematic review that analyzed 10 studies of 27,894 patients, Hamade et al 13 showed that for every 1% increase in the NDR, there was a 3.5% reduction in Barrett's neoplastic lesion identified in the postfollow-up endoscopy. This study has been the only one to currently demonstrate the inverse relationship, but this finding has not yet been supported by other studies.…”
Section: Issues With Ndr As a Qimentioning
confidence: 99%
See 2 more Smart Citations